2021
DOI: 10.1111/1756-185x.14178
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obstructive sleep apnea among patients with rheumatoid arthritis and its association with age and body mass index: A systematic review and meta‐analysis

Abstract: In a number of rheumatic diseases akin to rheumatoid arthritis (RA)-osteoarthritis, systemic lupus erythematosus, Sjögren syndrome, fibromyalgia, juvenile idiopathic arthritis, systemic sclerosis, spondyloarthritis, and Behçet syndrome-sleep abnormalities comprising reduced sleep, sleep fragmentation, and insomnia have been recognized. 1 Sleep apnea is an under-recognized comorbidity among rheumatology patients and its presence may adversely affect the evaluation of rheumatic disease activity and treatment res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…1 Through 8 included studies which enrolled a total of 37 285 patients, a high prevalence of OSA was found in patients with RA, and body mass index appeared to be a major risk factor for OSA as well. 1 Considering the complexity of both OSA and RA, several aspects warrant further discussion.…”
Section: Contentsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 Through 8 included studies which enrolled a total of 37 285 patients, a high prevalence of OSA was found in patients with RA, and body mass index appeared to be a major risk factor for OSA as well. 1 Considering the complexity of both OSA and RA, several aspects warrant further discussion.…”
Section: Contentsmentioning
confidence: 99%
“…We read with great interest the systematic review and meta‐analysis by Thakur et al on the prevalence and possible risk factors for obstructive sleep apnea (OSA) in patients with rheumatoid arthritis (RA) 1 . Through 8 included studies which enrolled a total of 37 285 patients, a high prevalence of OSA was found in patients with RA, and body mass index appeared to be a major risk factor for OSA as well 1 . Considering the complexity of both OSA and RA, several aspects warrant further discussion.…”
Section: Contentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sleep disorders are frequently associated with RA. A recent meta-analysis has shown that the incidence of obstructive sleep apnea syndrome (OSAS) is 29.8% among RA cohorts, however with a significant heterogeneity, and high BMI is the principal risk factor ( 56 ). Although the epidemiology of sleep disorders is still blurred in RA-ILD, it is reasonable to consider OSAS as a significant complication in this subgroup of patients due to its relevance in other ILDs, including IPF, and can cause an extremely poor sleep quality that correlates with poor quality of life ( 57 , 58 ).…”
Section: Introductionmentioning
confidence: 99%